(untitled) (JURNAL GEOCELEBES, 2023)
Pasaran Island is a small island connected to the mainland island of Sumatra and located in Bandar Lampung. Pasaran Island is one of the supports for the economy in Bandar Lampung. This is in line with the 2011-2030 RTRW of Bandar Lampung as a strategic minapolitan area (Pasaran and Lempasing) in driving the regional economy and utilizing appropriate technology. Pasaran Island is dominated by fishing villages and seafood processing centers in Lampung. With a population of ± 1,233 people in an area of ​​± 12 Ha, Pasaran Island has the potential for continued development. A study of the density of Built-up Land on Pasaran Island needs to be carried out so that it can become important information and data in managing the development of Pasaran Island in the future. Remote sensing technology using UAV was carried out to retrieve accurate and precise large-scale mapping information that allows the level of detail of Built-up Land to be mapped according to the original conditions in the field. In this study, the data used to extract Built-up Land was orthophoto which was produced through visual interpretation methods, and to determine the level of density and efficiency of Built-up Land conditions the digitization method and spatial analysis was by calculating the area of ​​Built-up Land and calculating the percentage of Built-up Land density in Pasaran Island. The results of this study consisted of two maps, which are a map of the classification of Built-up and Non-Built-up Land and a map of Built-up Land types. The percentage of Built-up Land density was obtained from the calculation of the area of ​​Built-up Land classes divided by the area of ​​Pasaran Island, which resulted in a built-up density of 87.15% consisting of building classes, open land, public facilities, and road networks. As for the results of the non-built density was 12.84%, which consisted of a vegetation class where the vegetation is in the tree-shaped form, the population density and building density of Pasaran Island are low density.